Answer:
The output of the function when the input g = 2 ==> 14
The input of the function when the output is 1 ==> 3
An input and its corresponding output ==> (4, 22)
The absolute difference of the input and the output when the input is 6 ==> 24
Explanation:
Given the function, f(g) = 4g + 6:
✔️The output of the function when the input g = 2:
Substitute g = 2 into f(g) = 4g + 6 to find the output, f(g)
f(2) = 4(2) + 6
f(2) = 8 + 6
f(2) = 14
✔️The input of the function when the output is 18:
Substitute f(g) = 18 into f(g) = 4g + 6
18 = 4g + 6
18 - 6 = 4g + 6 - 6
12 = 4g
12/4 = 4g/4
3 = g
g = 3
✔️An input and its corresponding output:
If we plug in the pair of (4, 22) into f(g) = 4g + 6, the function would be true. That is f(4) = 22
Let's check it out below:
If we substitute g = 4 into f(g) = 4g + 6, the resulting output would be 22. Thus:
f(4) = 4(4) + 6
f(4) = 16 + 6
f(4) = 22
✔️The absolute difference of the input and the output when the input is 6:
Find the output of f(g) = 4g + 6 when the input, g = 6 by plugging in the value of g into f(g) = 4g + 6
f(6) = 4(6) + 6
f(6) = 24 + 6
f(6) = 30
Input = 6
Output = 30
The absolute difference = |6 - 30| = 24